Effects of Music Therapy Using Rhymes on Enhancing Social Skills and Behavioural Patterns in Children with Autism – An Experimental Study - Hemisha Jay Sheth; Moushumi Debnath; Deepashree Deka; Sherin Paulose; Manika Saxena; Yashasvi K. Damahe (The Bioscan, 2025)
Background: Autism is characterized by marked abnormalities in social interaction and communication as well as the presence of stereotypies and unusual interests. Concerning the presence of these abnormalities, this study was conducted to determine the effect of music therapy using rhymes which would be compared with therapy sessions without music therapy to enhance social skills and behavioural patterns in children with autism. Aims and Objectives: To determine the effects of music therapy using rhymes on enhancing social skills and behavioural patterns in children with autism. Materials and Methods: This study includes 24 participants and they were divided into two group’s i.e. experimental group and control group. Each group consists of 12 participants. Intervention given was therapy with music for experimental group anf therapy without rhymes for control group for 5 days per week for 4 weeks. Outcome measure used was CARS scale at baseline and at end of 4 weeks. Materials used were pen, pencil, CARS sheet, bubbles, animal toys, mobile phone and speaker. Results: After statistical analysis of data, results illustrated that experimental group and control group both showed improvements however significant improvements were seen in experimental group Conclusion: The study illustrated that significant effects were seen in experimental group. Hence, the study concludes that music therapy using rhymes does have significant effects on enhancing social and behavioural patterns in children with autism.